1997
DOI: 10.1007/bf02407097
|View full text |Cite
|
Sign up to set email alerts
|

Total mercury and methylmercury in sediments and in the polychaeteNereis diversicolor at Groot Buitenschoor (Scheldt estuary, Belgium)

Abstract: Abstract. Total mercury (Hg) and methylmercury (MeHg) concentrations were determined in sediments and in the polychaete worm Nereis diversicotor at 13 stations of a brackish water intertidal nmdflat of the Scheldt estuary. Hg and MeHg concentrations in sediments ranged from 144 to 1192 ng g-~ dw and from 0.8 to 6 ng g-~ dw, respectively. Both Hg and MeHg concentrations increased with an increase of organic matter (OM) content and fine grain fraction. In contrast, Hg accumulation hy N. diversicolor was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 26 publications
4
43
1
Order By: Relevance
“…2). The low water pH below the WHO, EPA and EU recommended pH values of 6.5-8.5 in most of the rivers increases metal bioavailability to organisms dwelling in those rivers and the high water pH values reduce metal bioavailability in the six other rivers as alkaline pH plays the role of trapping heavy metals [5,[17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The low water pH below the WHO, EPA and EU recommended pH values of 6.5-8.5 in most of the rivers increases metal bioavailability to organisms dwelling in those rivers and the high water pH values reduce metal bioavailability in the six other rivers as alkaline pH plays the role of trapping heavy metals [5,[17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…For the WHO guidelines for drinking-water quality, USEPA drinking-water standards and health advisories, and EU drinking-water regulations [13][14][15] [12,[18][19][20][21]. Similarly, the highest mean concentrations of Cd and Pb in sediment of Kafubu river at its confluence with Lubumbashi river (56 mgkg -1 dw and 342 mgkg -1 dw, respectively)…”
Section: Resultsmentioning
confidence: 99%
“…The very low OM content of the sediments and the pH in that river increase the metal bioavailability to organisms dwelling in those sediments. It has been reported that pH and organic matter are among the factors which favor heavy metal retention in soils [30,35], and that organic-rich soils or sediments play, for the same reasons as those presenting alkaline pH, the role of trapping heavy metals [6,7,35,36]. , respectively) and that of Pb in sediment of Kafubu river at its confluence with Lubumbashi river dw) and at the confluence of Lubumbashi river with Kafubu river (342 mgkg -1 dw), were higher than those respectively reported for the sediments of Winterbeek river [38].…”
Section: Resultsmentioning
confidence: 99%
“…Sediments have a high storage capacity of chemical pollutants [1,2] and act as a sink for trace metals [3][4][5][6][7]. sediments and in the water column, especially invertebrates and fish, but also for humans through human food chain [1,3,8,[13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation